Trophic isotopic carbon variation increases with pond’s hydroperiod: Evidence from an Austral ephemeral ecosystem - Tatenda Dalu (Nature Portfolio, 2017)
Abstract Trophic variation in food web structure occurs among and within ecosystems. The magnitude of variation, however, differs from system to system. In ephemeral pond ecosystems, temporal dynamics are relatively more important than in many systems given that hydroperiod is the ultimate factor determining the presence of an aquatic state. Here, using stable isotopes we tested for changes in trophic chain length and shape over time in these dynamic aquatic ecosystems. We found that lower and intermediate trophic level structure increased over time. We discuss these findings within the context of temporal environmental stability. The dynamic nature of these ephemeral systems seems to be conducive to greater levels of intermediate and lower trophic level diversity, with omnivorous traits likely being advantageous.